PENGEMBANGAN KETERAMPILAN BERPIKIR KRITIS MELALUI STORYTELLING BAGI CALON GURU BAHASA INGGRIS DI FKIP UNCEN - Monika Gultom; Ruth Naomi Nancy Wompere (JURNAL PENGABDIAN PAPUA, 2021)
This community service activity aims to introduce innovative English teaching methods Storytelling in English learning to prospective English teacher students in the FKIP UNCEN English Language Study Program to be better prepared and trained in developing English learning that is able to integrate the three aspects of educational taxonomy, namely cognitive, affective, and psychomotor. In learning using Storytelling conditions, storytellers have to be more creative using the language focus in telling stories they read to students and at the same time asking questions that are able to stimulate students to think critically using the target language correctly in order to create the meaningful interaction and natural learning environment between both the storytellers and their listeners. The specific purpose of this activity is to introduce the use of Storytelling in teaching and learning English classroom in the context of the foreign language teaching and learning, and how it is managed to build a learning atmosphere to support the development of target language skills as well as learners’ critical thinking skills through classroom interaction in the form of dialogue and questions given by speakers. This community service activity involved students of the VII semester English language study program who take the Curriculum and Material Development course, conduct for about six month including the selection and deepening of the story that will be used for storytelling, a list of questions that have the potential to stimulate critical thinking skills, enrichment story material, implementation of community service activities, and seminars as a result of community service activities. This activity is useful for the readiness of prospective English teacher students in the English Education Study Program FKIP UNCEN in applying their knowledge and knowledge after completing their studies. Keywords: Critical Thinking Skills; Storytelling; Prospective English Teacher